Creating an Authorizing Environment to Care for Country - Teagan Shields; Leah Talbot; Jack Pascoe; Josh Gilbert; Jade Gould; Barry Hunter; Stephen vanLeeuwen (Conservation Letters)
ABSTRACT Typically, Western Science approaches the study of complex systems by examining the component parts outside of their contextual relationships. In contrast, Indigenous people continue to advocate the need for land and seascape approaches that include all aspects of life, particularly the special relationship between Kin (people), Country, and Knowledge. Globally, Indigenous people are lobbying for environmental research to take a rights‐based approach that improves economic opportunities; confers greater authority over the stewardship of Country; delivers equity in managing Country; emboldens control to integrate knowledge systems; values and promotes culture; and recognizes Indigenous self‐determination. In Australia, the National Indigenous Environment Research Network (NIERN) proposal offers a solution that supports the rights‐based approach driven by Indigenous Australians through the establishment of a community of practice guided by Indigenous researchers and Indigenous Knowledge holders. We describe this Indigenous‐led solution to the self‐determination of Indigenous environmental research priorities by exploring the concept, the authorizing environment, and the mutual benefits that could be delivered by such a network. The empowerment of Indigenous people in research is possible if an all‐of‐system approach is taken. This approach must involve Indigenous people in all decision‐making processes including the development of research priorities, the design of methodologies, the interpretation of findings, and finally the evaluation of outputs and outcomes.